A study on mechanical properties and thermal properties of UHMWPE/MWCNT composite fiber with MWCNT content and draw ratio. (June 2022) - Eun, Jong Hyun; Kim, Do Hyun; Jang, In Uk; Sung, Sun Min; Kim, Min Seong; Choi, Bo Kyoung; Kang, Sun Woo; Kim, Min Soo; Lee, Joon Seok
In this study, the mechanical properties and thermal properties of ultra-high molecular weight polyethylene (UHMWPE)/multi wall carbon nanotubes (MWCNT) composite fiber were investigated with different weight percent of the MWCNT contents and draw ratio. To verified the thermal properties of the MWCNT/UHMWPE composite fiber, DSC and TGA analysis were performed. The addition of MWCNT and the higher draw ratio improved the thermal properties of the UHMWPE composite fiber by improving the crystallinity of the polymer. By adding 2 wt% MWCNT, UHWMPE fibers with tensile strengths of 3.85 GPa and young's modulus of 27.43 GPa could fabricated. In comparison with the pristine UHMWPE fiber with same draw ratio conditions, there values shows increases of 21% in tensile strength and 16% in young's modulus value. However, in the case of the specimens in which the MWCNT content of 6wt% and 10wt% was added to the UHMWPE fiber, the tensile strength and tensile modulus gradually decreased. We proved by experimentally that the mechanism of strengthening the tensile strength of UHMWPE fibers with MWCNT content of 2wt% is to block craze stretching and reduce defects inside the amorphous region by improving the crystalline region. However, the MWCNT contents is increased by 6wt% or more, the nanofillers start to agglomerate and act as impurities and stress concentration factors, thereby reducing the mechanical properties of the UHMWPE composite fiber.